Maternal plasma soluble neuropilin‐1 is downregulated in fetal growth restriction complicated by abnormal umbilical artery Doppler: a pilot study. (1st November 2021) - Porter, B.; Maulik, D.; Babbar, S.; Schrufer‐Poland, T.; Allsworth, J.; Ye, S. Q.; Heruth, D. P.; Lei, T.
ABSTRACT: Objectives: Placental expression of neuropilin‐1 (NRP1), a proangiogenic member of the vascular endothelial growth factor receptor family involved in sprouting angiogenesis, was recently discovered to be downregulated in pregnancies with fetal growth restriction (FGR) and abnormal umbilical artery (UA) Doppler. Soluble NRP1 (sNRP1) is an antagonist to NRP1; however, little is known about its role in normal and FGR pregnancies. This study tested the hypotheses that, first, sNRP1 would be detectable in maternal circulation and, second, its concentration would be upregulated in FGR pregnancies compared to those with normal fetal growth and this would correlate with the severity of the disease as assessed by UA Doppler. Methods: This was a prospective case–control pilot study of 40 singleton pregnancies (20 FGR cases and 20 uncomplicated controls) between 24 + 0 and 40 + 0 weeks' gestation followed in an academic perinatal center from January 2015 to May 2017. FGR was defined as an ultrasound‐estimated fetal weight < 10 th percentile for gestational age. The control group was matched to the FGR group for maternal age and gestational age at assessment. Fetal ultrasound biometry and UA Doppler were performed using standard protocols. Maternal plasma sNRP1 measurements were performed using a commercially available ELISA. Results: Contrary to the study hypothesis, maternal plasma sNRP1 levels were significantly decreased in FGR pregnancies as compared to those with normal fetal growth (137.4 ± 44.8 pg/mL vs 166.7 ± 36.9 pg/mL; P = 0.03). However, there was no significant difference in sNRP1 concentration between the control group and FGR pregnancies that had normal UA Doppler. Plasma sNRP1 was downregulated in FGR pregnancies with elevated UA systolic/diastolic ratio ( P = 0.023) and those with UA absent or reversed end‐diastolic flow ( P = 0.005) in comparison to FGR pregnancies with normal UA Doppler. This suggests that biometrically small fetuses without hemodynamic compromise are small‐for‐gestational age rather than FGR. Conclusions: This study demonstrated a significant decrease in maternal plasma sNRP1 concentration in growth‐restricted pregnancies with fetoplacental circulatory compromise. These findings suggest a possible role of sNRP1 in modulating fetal growth and its potential as a biomarker for FGR. © 2021 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.